Hubungan Tingkat Konsumsi Zat Besi Dan Pola Menstruasi Dengan Kejadian Anemia Pada Remaja Putri Di Smp Kristen 1 Surakarta - SIRAIT, APRELLYIA LORENCYA (2016)
Introduction: Iron deficiency anemia may cause by low iron intake inhibited, absorption of iron, the increased need for iron and iron loss. Iron loss may be due to menstrual pattern. Menstrual cycles shorter and longer time periods will cause spending more and more iron which can lead to anemia. Based on a preliminary survey in SMP Kristen 1 Surakarta student that suffered anemia was 39.04% Destination: Knowing the correlation between consumption of iron and menstrual patterns with the incidence of anemia among adolescent girls in SMP Kristen 1 Surakarta. Research Methods: This study used cross sectional design. The number of research subjects were 51, selected by simple random sampling method. Iron consumption level data obtained using 24-hour recall food consumption for 3 days were not consecutive, menstrual patterns obtained by interviewing students about the menstrual cycle and length for last 3 months. Test data normality using the Kolmogorov-Smirnov Test and test relationships using Person Product Moment Correlation test for levels of iron consumption, while the pattern of menstruation (the menstrual cycle and long periods using Spearman Rank correlation test. Results: The results showed that of subjects consume insufficient iron 60.8%, subjects who had normal menstrual cycle is 54.9%, most of the subjects had a normal menstrual long by 58.8% and measured levels of hemoglobin showed mostly normal 52.9%. The result of the correlation between iron consumtion, the menstrual cycle, length periods with the of anemia that is p = 0.000. Conclusion: There is a correlation between consumption level of iron and menstrual pattern (length of menstruation and menstrual cycles) and the incidence of anemia among adolescent girls in SMP Kristen 1 Surakarta